News and Media Literacy for Speaking Practice - Andi Idayani; Betty Sailun; Sri Yuliani (STAI Hubbulwathan Duri, 2022)
Speaking is a significant and fundamental skill that may help students enhance their ability to communicate with their classmates verbally. Henceforth, instructors or teachers need to incorporate some educating media which can develop the students’ English speaking competence. Therefore, this study aims to discover the viability of news and media literacy for speaking practice at an advanced education level. The researchers used experimental research and took two groups as the sample of this study. There were experimental groups in class 4b and a control group in 4a class that comprised 35 students for each class. Moreover, the speaking test, mainly pre-test and post-test in both experimental class and control class, was also used as gathering information of the research. This research found that the difference between pre-test and post-test average speaking practice results was -24.540 to -17,689, with a 95 percent confidence range of -24.540 to -17,689 for this finding. Finally, this study discovered an average difference in students' speaking practice between the pre-test and post-test. Therefore, enhancing students use of news and media literacy is necessary for speaking practice and teachers need to encourage students’ use of technology to find out online sources as media literacy in learning the second language. They have various kinds of information from media sources and improve the advanced vocabulary that they used while practising speaking with their classmates. To summarize, integrating news and media literacy has a substantial impact on enhancing students' speaking skills among four-semester students of English Language Education in Pekanbaru.